Development of Student Worksheets Integrated with the Qur’an and Hadith on Plant Transport System Material - Ratu Permatasari; Putri Arya Salsabila; Fuji Barlian Andini; Ummi Hiras Habisukan; Weni Lestari; Irmansyah (Indonesian Journal of Biology Education, 2026)
This study aims to develop a Student Worksheet (LKPD) integrated with Qur’anic verses and Hadith for the topic of plant transport systems in Grade XI Biology. The development process employed the ADDIE model, covering the Analyze, Design, and Develop stages, which included needs analysis, instructional design, and the preparation of the initial product. The LKPD was validated by four experts content, media, language, and Islamic studies experts. All validation aspects were classified as highly valid after revisions were made based on expert feedback. In addition, a practicality test administered to students produced scores ranging from 81.33% to 98.66%, indicating a very practical category. These findings suggest that the developed LKPD is feasible for use, easy to understand, and capable of guiding students to learn more effectively. The integration of Islamic values is also considered to enrich students understanding of biological concepts through strengthened spiritual meaning. This study recommends the use of the LKPD as a supporting learning resource and encourages further development in the implementation and evaluation stages for future research.